2018
DOI: 10.3389/fpsyg.2018.01481
|View full text |Cite|
|
Sign up to set email alerts
|

A Crossover Study From a Gender Perspective: The Relationship Between Job Insecurity, Job Satisfaction, and Partners’ Family Life Satisfaction

Abstract: Background: In the last years, many changes have involved the labor context: new ways of working, more flexibility and uncertainty, new and more insecure job contracts. In this framework, perceived job insecurity, worker’s perception about potential involuntary job loss, has received renewed interest, also for those workers with a permanent contract in Italy. Consequences of job insecurity on work-related outcomes such as job satisfaction have been demonstrated; nevertheless, its possible effects outside the w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
38
0
15

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(55 citation statements)
references
References 83 publications
2
38
0
15
Order By: Relevance
“…This perspective emphasizes the sustainable development of every person, by facilitating the flourishing of own skills and an improvement of own quality of life, which, thus, becomes not only a personal growth but also a benefit of the community of belonging and progress. In summary, also in the perspective of the psychology of sustainability and sustainable development [4][5][6] more research is needed to unveil the complexity of the relationships between these variables, and other dimensions, such as life satisfaction and job insecurity need to be explored [2,61].…”
Section: Discussionmentioning
confidence: 99%
“…This perspective emphasizes the sustainable development of every person, by facilitating the flourishing of own skills and an improvement of own quality of life, which, thus, becomes not only a personal growth but also a benefit of the community of belonging and progress. In summary, also in the perspective of the psychology of sustainability and sustainable development [4][5][6] more research is needed to unveil the complexity of the relationships between these variables, and other dimensions, such as life satisfaction and job insecurity need to be explored [2,61].…”
Section: Discussionmentioning
confidence: 99%
“…Job insecurity merupakan kondisi psikologis sese-orang (pegawai) yang ditunjukkan dengan adanya perasaan bingung dan tidak aman karena kondisi lingkungan organisasi yang berubah-ubah (perceived impermanence). Persepsi tentang job insecurity yang muncul selalu diikuti oleh berbagai dampak negatif psikologis seperti depresi dan kecemasan serta sejumlah sikap di tempat kerja, seperti kepuasan kerja, motivasi, dan komitmen pegawai (Emanuel et al, 2018). Menurunnya kepuasan kerja juga merupakan sebuah sikap yang ditunjukkan pegawai karena terdapat sejumlah aspek pada pekerjaan yang dirasakan tidak terpenuhi, seperti gaji, peluang promosi, kondisi kerja, hubungan dengan atasan, dan hubungan dengan sejawat, serta lingkungan pekerjaan (Riana, et al, 2018).…”
Section: Pendahuluanunclassified
“…The Interdependence Theory [ 22 ] recognizes the importance of mutual influences (i.e., interdependence), while the Family Systems Theory [ 23 ] underscores the interdependence between individuals, so that individuals involved in reciprocal relationships, such as family members, can influence one another in their thoughts, emotions and behaviors. Consistent with these theories, research has shown that life satisfaction [ 14 , 24 ], job satisfaction [ 25 ], satisfaction with family life [ 14 , 26 ] and satisfaction with food-related life [ 14 , 27 ] are correlated between members of a couple. Therefore, both theories make it possible to hypothesize that an individual’s life satisfaction is not only influenced by their own satisfaction in different life domains but also by their partner’s satisfaction in different life domains in married or cohabiting couples, which, to the best of the authors’ knowledge, has not been previously assessed.…”
Section: Introductionmentioning
confidence: 97%
“…In addition to the differences in women’s socialization [ 36 ], Westman [ 70 ] suggested that gender differences may be related to the distinct ways men and women react to what happens to their partner, their degree of involvement in family affairs and in traditional gender-based demands and expectations. Namely, women tend to be more involved in family activities and seem to be more responsive to situations affecting their male partners than men [ 26 ].…”
Section: Introductionmentioning
confidence: 99%